Formulation And Evaluation Of Anti-Aging Face Spray Preparation From Ethanol Extract Of Rosemary Leaf (Salvia Rosmarinus Spenn.) And Antioxidant Activity Test Using The DPPH Method - Inna Myesha; Rafita Yuniarti; Minda Sari Lubis; Zulmai Rani (Jurnal EduHealth, 2025)
The skin's need to prevent premature aging requires skincare products with antioxidant content. A popular skincare product used today is face spray. Face sprays containing active ingredients as antioxidants are beneficial in preventing premature aging. One of the plants known for its antioxidant properties is rosemary leaf (Salvia rosmarinus Spenn.). The development of face spray with the addition of rosemary leaf extract is a form of utilizing plants in cosmetic products. This study is an experimental research. In this study, rosemary leaf ethanol extract face spray was formulated with concentrations of 0%, 0.5%, 1%, 3%, and 5%. Evaluation included physical quality, hedonic test, irritation test, antioxidant activity test, and anti-aging effectiveness test. Anti-aging data were analyzed using SPSS. Based on physical quality evaluation, the face spray formula with the best physical quality was found at extract concentrations of 1%, 3%, and 5%, with observations indicating stable organoleptic properties, pH within the skin range of 4.5-6.5, good spreading ability, no coarse particles or clumping, and stable formulations after 28 days of room temperature stability testing (25°C) and 6 cycle cycling tests. The formulations also showed no irritation to the skin. In the antioxidant activity test, the 0.5% extract concentration exhibited moderate antioxidant activity, while concentrations of 1%, 3%, and 5% showed strong antioxidant activity. In the anti-aging effectiveness test using a skin analyzer, each formula demonstrated significant differences in skin changes with a p-value of <0.05.